Influence of sodium bicarbonate on performance and hydration in lightweight rowing - Kupcis, P. D.; Slater, G. J.; Pruscino, C. L.; Kemp, J. G. (International Journal of Sports Physiology and Performance, 2012)
Purpose: The effect of sodium bicarbonate (NaHCO3) ingestion on prerace hydration status and on 2000 m ergometer performance in elite lightweight rowers was examined using a randomized, cross-over, double- blinded design. Methods: To simulate body mass (BM) management strategies common to lightweight rowing, oarsmen reduced BM by approx. 4% in the 24 h preceding the trials, and, in the 2 h before performance, undertook nutritional recovery consisting of mean 43.2 kJ/kg, 2.2 g of CHO per kilogram, 31.8 mg of Na+ per kilogram, 24.3 mL of H2O per kilogram, and NaHCO3 (0.3 g of NaHCO3 per kilogram BM) or placebo (PL; 0.15 g of corn flour per kilogram BM) at 70 to 90 min before racing. Results: At 25 min before performance, NaHCO3 had increased blood pH (7.48 ± 0.02 vs PL: 7.41 ± 0.03, P = .005) and bicarbonate concentrations (29.1 ± 1.8 vs PL: 23.9 ± 1.6 mmol/L, P < .001), whereas BM, urine specific gravity, and plasma volume changes were similar between trials. Rowing ergometer times were similar between trials (NaHCO3: 397.8 ± 12.6; PL: 398.6 ± 13.8 s, P = .417), whereas posttest bicarbonate (11.6 ± 2.3 vs 9.4 ± 1.8 mmol/L, P = .003) and lactate concentration increases (13.4 ± 1.7 vs 11.9 ± 1.9 mmol/L, P = .001) were greater with NaHCO3. Conclusion: Sodium bicarbonate did not further enhance rehydration or performance in lightweight rowers when undertaking recommended post-weigh-in nutritional recovery strategies.